PERAN BAKTERI ASAM LAKTAT (BAL) PADA TEH KOMBUCHA SEBAGAI SUMBER PROBIOTIK - Muhamad Ikhsan Prawira Negara; Mona Meilani (Jurnal Fakultas Teknik Kuningan, 2023)
Kombucha tea is widely used as a traditional medicine to stabilize metabolism and remove toxins so that it can improve digestion. Probiotics function to balance the intestinal microflora so that they can treat diarrheal infections. The chemical composition of kombucha tea also has health benefits, namely the content of polyphenols which are used as antioxidants. The purpose of writing is to determine the role of lactic acid bacteria (LAB) in kombucha tea as a source of probiotics. Some of the research results can be concluded that lactic acid bacteria in the kombucha tea fermentation process are very influential on health because there is a source of probiotics in it.